Improving critical thinking skills of master students through problem-based learning model (Journal of Educational Sciences, 2023)
Critical thinking is one of the most essential skills in the education system of modern society. Inthe field of education, many methods and techniques are used to develop this skill. In this regard, theproblem-based learning method can be considered as the most effective of the various methods. It wasinvestigated the efficiency of Problem-Based Learning (PBL) model as a useful strategy for improvingEnglish language learners’ critical thinking skills. The participants of this study were 34 Master Studentsof Academic Writing program of Khoja Akhmet Yassawi International Kazakh-Turkish University. Englishlanguage learners were separated into experimental and control groups. The author used pre andpost tests as a data collection instrument. In order to analyze the test results a quantitative method anddescriptive statistical analysis were applied. The test scores were measured according to the six indicatorsof Bloom’s Taxonomy thinking levels. The study lasted five weeks and the experimental group wastaught online via Google classroom platform. In this research, a mind mapping strategy was used as abrainstorming tool to define and solve problems. It can be noted that the experimental group’s posttestscores and learning outcomes were significantly improved. The experimental group achieved highscores from understanding and evaluation indicators, scoring 79% and 76% higher than the averagescores respectively. This means that they can understand and evaluate any information they read orhear. While the other indicators, namely memorization (65%), application (68%) creation (61%) andanalysis (51%), were also higher than the previous test scores. The latest results of the study identifiedthe problem-oriented learning (PBL) model as the most effective method for developing critical thinkingand recommend its independent application in any educational institution. It was also found that theintegrated application of the problem-based learning (PBL) model with the mind mapping strategy canimprove English language learners’ critical thinking skills.Key words: critical thinking, Bloom’s Taxonomy, problem-based learning (PBL), mind map, Mind-Meister.